2012
DOI: 10.3758/s13421-012-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

List-method directed forgetting: The forget cue improves both encoding and retrieval of postcue information

Abstract: In list-method directed forgetting, people are cued to forget a previously studied item list and to learn a new list instead. Such cuing typically leads to forgetting of the first list and to memory enhancement of the second, referred to as list 1 forgetting and list 2 enhancement. In the present study, two experiments are reported that examined influences of items' serial learning position in a list and the two lists' output order on list-method directed forgetting. The results show that list output order inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
73
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 40 publications
(76 reference statements)
10
73
2
Order By: Relevance
“…On the other hand, the finding is in line with results from more recent LMDF work (e.g., Delaney & Sahakyan, 2007;Delaney et al, 2009;Sahakyan, 2004;Zellner & Bäuml, 2006), which shows that the enhancement is not always present in LMDF. Pastötter et al (2012) recently demonstrated that the failure to find the enhancement effect often occurs when, at test, the precue items are recalled first and the postcue items are recalled last, a procedure that was also chosen in the present experiment. The General Discussion section below provides a theoretical explanation of this output order effect and discusses the issue further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the finding is in line with results from more recent LMDF work (e.g., Delaney & Sahakyan, 2007;Delaney et al, 2009;Sahakyan, 2004;Zellner & Bäuml, 2006), which shows that the enhancement is not always present in LMDF. Pastötter et al (2012) recently demonstrated that the failure to find the enhancement effect often occurs when, at test, the precue items are recalled first and the postcue items are recalled last, a procedure that was also chosen in the present experiment. The General Discussion section below provides a theoretical explanation of this output order effect and discusses the issue further.…”
Section: Discussionmentioning
confidence: 99%
“…This has recently been documented in a meta-analysis and has been shown experimentally by varying list output order at test (Pastötter et al, 2012). Enhancement of the postcue items in response to the forget cue has often been attributed to reduced interference of the precue items at test (e.g., Geiselman et al, 1983;Sahakyan & Kelley, 2002).…”
Section: Theoretical Implications For Lmdf Accountsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results replicate the findings of many recent studies, in which no list 2 enhancement arose when at test list 1 was recalled first and list 2 was recalled second (e.g., Delaney & Sahakyan, 2007;Delaney, Nghiem, & Waldum, 2009;Pastötter & Bäuml, 2010;Zellner & Bäuml, 2006), a procedure that was also chosen in the present experiment. Indeed, conducting a meta-analysis on the influence of list output order on LMDF, Pastötter, Kliegl, and Bäuml (2012) recently showed that the forget cue induces facilitation for list 2 items mainly when list 2 is tested first and shows hardly any facilitatory effect when list 2 is tested last. The present finding of no list 2 enhancement thus very likely arose due to chosen list output order.…”
Section: Discussionmentioning
confidence: 99%